2012
DOI: 10.7314/apjcp.2012.13.7.3233
|View full text |Cite
|
Sign up to set email alerts
|

MSP58 Knockdown Inhibits the Proliferation of Esophageal Squamous Cell Carcinoma in Vitro and in Vivo

Abstract: Esophageal carcinoma (EC) is one of the most aggressive cancers with a poor prognosis. Understanding the molecular mechanisms underlying esophageal cancer progression is a high priority for improved EC diagnosis and prognosis. Recently, MSP58 was shown to behave as an oncogene in colorectal carcinomas and gliomas. However, little is known about its function in esophageal carcinomas. We therefore examined the effects of MSP58 knockdown on the growth of esophageal squamous cell carcinoma (ESCC) cells in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Conversely, overexpression of NDRG2 has been measured in decreased cancer cell growth (Deng et al, 2003;Choi et al, 2007;Yang et al, 2010). NDRG2 can inhibit MSP58 (a 58-kD nuclear microspherule protein)-induced cell proliferation in glioma cells or colon cancer cells (Xu et al, 2012). Consistent with all the previous results, we observed that NDRG2 expression was decreased in two NB cell lines, SK-N-SH and SH-SY5Y ( Figure 1A).…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, overexpression of NDRG2 has been measured in decreased cancer cell growth (Deng et al, 2003;Choi et al, 2007;Yang et al, 2010). NDRG2 can inhibit MSP58 (a 58-kD nuclear microspherule protein)-induced cell proliferation in glioma cells or colon cancer cells (Xu et al, 2012). Consistent with all the previous results, we observed that NDRG2 expression was decreased in two NB cell lines, SK-N-SH and SH-SY5Y ( Figure 1A).…”
Section: Discussionsupporting
confidence: 80%
“…Drosophila MCRS2 is co-purified with RNA polymerase II complexes and is required for normal levels of cycling gene expression ( 37 ). A previous study revealed that MCRS1 and MCRS2 are involved in cell cycle regulation and carcinogenesis ( 20 , 32 ). Carcinoembryonic antigen (CEA) was first identified in 1965 ( 38 ) and has now become the most widely used antigen for diagnosing and for monitoring the prognostic significance of CRC ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…TOJ3 (a quail homolog of MCRS1) behaves as an oncogene during fibroblast transformation, and this transformation activity can be suppressed by the tumor suppressor PTEN [ 8 , 9 ]. MCRS1 overexpression has been documented in a variety of human cancers, and this overexpression was found to induce the proliferation of cancer cells [ 3 , 10 12 ]. In the present study, we observed that MCRS1 overexpression promoted the epithelial-mesenchymal transition (EMT) and metastasis in NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%
“…MCRS1 overexpression has been documented in a variety of human tumors [ 3 , 10 12 ]; however, the molecular mechanisms underlying MCRS1 alteration remain elusive. In this study, we investigated the mechanisms of MCRS1 regulation in NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%